The N6-methyladenosine demethylase ALKBH5 regulates the hypoxic HBV transcriptome - Tsukuda, S; Harris, JM; Magri, A; Balfe, P; Siddiqui, A; Wing, PAC; McKeating, JA (Public Library of Science, 2024)
Chronic hepatitis B is a global health problem and current treatments only suppress hepatitis B virus (HBV) infection, highlighting the need for new curative treatments. Oxygen levels influence HBV replication and we previously reported that hypoxia inducible factors (HIFs) activate the basal core promoter (BCP). Here we show that the hypoxic-dependent increase in BCP-derived transcripts is dependent on N6-methyladenosine (m6A) modifications in the 5' stem loop that regulate RNA half-life. Application of a probe-enriched long-read sequencing method to accurately map the HBV transcriptome showed an increased abundance of pre-genomic RNA under hypoxic conditions. Mapping the transcription start sites of BCP-RNAs identified a role for hypoxia to regulate pre-genomic RNA splicing that is dependent on m6A modification. Bioinformatic analysis of published single cell RNA-seq of murine liver showed an increased expression of the RNA demethylase ALKBH5 in the peri-central low oxygen region. In vitro studies with a human hepatocyte derived HepG2-NTCP cell line showed increased ALKBH5 gene expression under hypoxic conditions and a concomitant reduction in m6A-modified HBV BCP-RNA and host RNAs. Silencing the demethylase reduced the level of BCP-RNAs and host gene (CA9, NDRG1, VEGFA, BNIP3, FUT11, GAP and P4HA1) transcripts and this was mediated via reduced HIFα expression. In summary, our study highlights a previously unrecognized role for ALKBH5 in orchestrating viral and cellular transcriptional responses to low oxygen.